Resilience among asylum seekers living with HIV - Orton Lois; Griffiths Jane; Green Maia; Waterman Heather (BMC, 2012)
Abstract Background A small body of evidence demonstrates the challenges faced by migrant communities living with HIV but has yet to consider in-depth the experience of asylum seekers whose residency status is undetermined. The overall aim of our study was to explore the experiences of those who are both living with HIV and seeking asylum. This paper focuses on the stressors precipitated by the HIV diagnosis and by going through the asylum system; as well as participants' resilience in responding to these stressors and the consequences for their health and wellbeing. Methods We conducted an ethnographic study. Fieldwork took place in the UK between 2008-2009 and included: 350 hours of observation at voluntary services providing support to black and minority ethnic groups living with HIV; 29 interviews and four focus group discussions with those who were seeking asylum and living with HIV; and 15 interviews with their health and social care providers. Data were analysed using the constant comparative method. Results There were three main stressors that threatened participants' resilience. First, migration caused them to leave behind many resources (including social support). Second, stigmatising attitudes led their HIV diagnosis to be a taboo subject furthering their isolation. Third, they found themselves trapped in the asylum system, unable to influence the outcome of their case and reliant on HIV treatment to stay alive. Participants were, however, very resourceful in dealing with these experiences. Resilience processes included: staying busy, drawing on personal faith, and the support received through HIV care providers and voluntary organisations. Even so, their isolated existence meant participants had limited access to social resources, and their treatment in the asylum system had a profound impact on perceived health and wellbeing. Conclusions Asylum seekers living with HIV in the UK show immense resilience. However, their isolation means they are often unable to deal with their treatment in the asylum system, with negative consequences for their perceived health and wellbeing.